Analysis of the annual variability of premature born lives and deaths regarding birth weight in ES - Marvila Santos, Isabella; Morine Saloum, Michel; Moura Dias, Fabiano; do Prado Pacheco, Juliana; Navarro Schneider, Guilherme (Seven Editora, 2023)
Prematurity is one of the main factors of infant mortality. Thus, the objective of this study was to analyze the annual variability of live births and premature deaths concerning the birth weight range in the state of Espirito Santo, Brazil. The period studied was between the years 2000 to 2020 using a historical series of data from the Information System for Live Births - SINASC and the Mortality Information System - SIM. In the records analyzed, a total of 1,135,352 live births were obtained, of which 73,420 (6.47%) were premature, born between 22 and 36 weeks of gestational age, and weighing more than 1500 g. The highest proportion of premature newborns, referring to birth weight, occurred for weights from 1500 to 2500 g (Low Birth Weight). The highest proportions of premature deaths about birth weight were for the lowest weight ranges. The percentage of deaths related to gestational age was lower for the age group of 32-36 weeks. DOI: https://doi.org/10.56238/colleinternhealthscienv1-135